Validity and Practicality of Newton's Law Interactive E-Worksheet with The Assistance of Liveworksheets - Siahaan, Sardianto Markos; Komarudin, Wawan Ahmad (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
The demand for independent learning, both at home and in school, highlights the importance of providing instructional materials in the form of interactive student worksheets (e-Worksheets) to support continuous scientific learning activities. This study aims to develop an interactive electronic worksheet (e-Worksheets) utilizing the Liveworksheets platform, specifically designed for high school students studying Newton’s Laws, and to evaluate its validity and practicality. The research employed the Alessi and Trollip development model, which consists of three phases: planning, design, and development. Content validity was assessed through expert judgment using Aiken’s V, while practicality was measured using student response questionnaires. The research subjects were students from Class XF at Senior High School 1 Muara Padang. Data analysis results indicated that the developed interactive e-Worksheets is both valid and practical, with a validity score of 95.3% and a practicality score of 83.8%. These results categorize the e-Worksheets as highly valid and highly practical, making it suitable for classroom implementation. However, this study only addresses the validity and practicality aspects and does not assess the effect of the e-Worksheets on students’ learning outcomes.